The Effectiveness of Active Learning Approach to Mastery of Public Speaking in Malay and Self-Confidence of the Malay Language Program Students Thaksin Universtiy - Isayah, Kamaruddin (MENARA : Journal of Islamic and Contemporary Issues, 2024)
This research article is part of a study on the level of mastery of public speaking in the Malay language and the level of self-confidence among students of the Malay Language major, Universiti Thaksin, through an active learning approach in the form of a quantitative study. This study is based on two objectives, namely to identify the level of mastery of public speaking in Malay among students of the Malay Language major, Universiti Thaksin based on the active learning approach, and to identify the level of self-confidence of students when delivering public speeches in the Malay language in specific situations. This study uses a quantitative methodology through a survey method on a sample selected through purposive sampling. The respondents consist of fourth-year students from the Malay Language Program, Thaksin University. A questionnaire was used on 30 respondents taking the Public Speaking course to gather data on self-confidence in public speaking. Public speaking exercises in specific situations were also used and evaluated to assess the proficiency of the respondents in the Malay language. The data collected was analyzed using Statistical Packages for the Social Science (SPSS) version 17.0. The data analysis used descriptive methods such as discrimination, percentages, standard deviations, and t-tests (Dependent Sample). The results of this study indicate that after students were exposed to active learning, their performance in public speakingaveraged = 11.40, which is significantly higher than before being exposed to active learning, where the average was only = 9.43. This means that students achieved reasonable progress in mastering the Malay language after the active learning approach was applied to their learning. Regarding the level of self-confidence in public speaking, it was found that most students rated their self-confidence in most aspects at a moderate level with an average of only = 3.50. The findings of this study prove that there are several factors contributing to weaknesses in public speaking in the Malay language among the respondents. Among them, the majority do not have a foundation in the Malay language, do not have opportunities to communicate in Malay, lack practice in language skills activities, and lack confidence in speaking Malay.